Policy Alienation in the Implementation of the Papua Indigenous People Empowerment Program in Sorong City - Zarni Adia Purna (ASHA Publishing, 2026)
This study examines the phenomenon of policy alienation in the implementation of the Papua Indigenous People (Orang Asli Papua/OAP) Empowerment Program in Sorong City, West Papua Province, Indonesia. Policy alienation refers to the psychological and structural disconnect experienced by street-level bureaucrats and target groups when implementing or receiving public policies. Using a qualitative descriptive approach with in-depth interviews, observation, and document analysis, this research explores how front-line implementers and indigenous beneficiaries experience alienation across four dimensions: powerlessness, meaninglessness, normlessness, and social isolation. Data were collected from purposively selected informants, including OAP community leaders, local government officials, and program beneficiaries in Sorong City. The findings reveal that policy alienation emerges significantly in the program's implementation, primarily due to the top-down policy design that marginalizes indigenous voices, bureaucratic rigidity, limited participation of OAP communities, and weak coordination among relevant agencies. Front-line workers reported feelings of powerlessness in adapting policies to local cultural contexts, while beneficiaries expressed a sense of meaninglessness due to program outcomes that did not correspond to their actual needs and aspirations. These alienation dynamics ultimately undermine the effectiveness and sustainability of OAP empowerment initiatives. The study contributes theoretically to the policy alienation literature within the Indonesian indigenous people empowerment context and offers practical recommendations for participatory policy redesign to bridge the gap between policy intent and implementation reality.